Tribotronic components: A revolution transforming machine elements into cyber-physical systems - Ian Sherrington; Sergei Glavatskih (Friction)
This paper explores the development of a subject called “tribotronics”, the science of actively controlled tribological elements, and considers the potential of tribotronics as part of a revolutionary machine element design for the future. It presents a “state-of-the-art” assessment of some devices that can be considered “tribotronic” and are currently in common use, as well as a review of examples of recent progress in research in tribotronics. It also presents a “perspective” on the future challenges and likely developments in the subject, including the integration of tribotronics with developments in other fields of digital technology, such as Industry 4.0, the “Internet of Things (IoT)”, and machine learning (ML), potentially leading to “cyber tribotronic systems”. In conclusion, tribotronics will contribute significantly to transforming the design of the components and machines of the present day into cyber-physical systems in the future.